Black–White and Male–Female Differences in Criminal Thinking: Examining Instrumental and Expressive Motives for Crime in Federal Supervisees - Walters, Glenn D. (The prison journal, 2018)
Using 2,000 federal supervisees comprised of 500 White males, 500 Black males, 500 White females, and 500 Black females, this study evaluated whether race and sex are differentially associated with proactive and reactive criminal thinking. It was predicted that proactive criminal thinking would be higher in Black than White supervisees and that reactive criminal thinking should be higher in female than male supervisees. Results revealed that instrumental motives for crime, as represented by proactive criminal thinking, were more prevalent in Black male offenders, and expressive motives for crime, as represented by reactive criminal thinking, were more prevalent in White female offenders.